Complications related to the postoperative period of surgeries resulting from trauma: an integrative review (Research, Society and Development, 2023)
Introduction. Trauma surgery is an extremely delicate procedure because there is a great loss of blood volume, generally causing a serious alteration in hemodynamics. Due to this, the immune system and related coagulation is compromised, leading to infection and even death. Objective: To analyze the main complications related to the postoperative period of trauma and their main consequences on the patient's quality of life. Methodology: This study is an integrative literature review. The databases of scientific articles were used to perform the searches: US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) Latin American and Caribbean Literature in Health Sciences (LILACS) and Biblioteca Virtual em Saúde (BVS) of scientific data up to December 8, 2022, in English, Portuguese and Spanish. The articles used are from the period from 2000 to 2022. The keywords “emergency” AND “trauma” AND “postoperative” were used. Result and discussion: The prompt emergency care after trauma is the main care to avoid a bad postoperative prognosis The main complications depend directly on the severity of the injury and the level of contamination to which the patient was exposed